“British Dialects in Animated Films: The Case of ‘Gnomeo & Juliet’ and its Creative Italian Dubbing” - Minutella, Vincenza (Status Quaestionis, 2017)
Gnomeo & Juliet (Kelly Asbury, 2011) is a humorous animated adaptation of Shakespeare’s tragedy in which the feuding families are portrayed as garden gnomes who, after racing and fighting on lawnmowers, stealing orchids and chatting with the Bard’s statue, live happily ever after, accompanied by Elton John’s songs. The film is set in the UK and most of the characters speak British English. This paper examines how dialects are exploited in the original English version to define characters and analyses the creative domestication process whereby the story is turned into an Italian tale by using Italian regional dialects.